Einstein Home - Pickford, Rollin:::::::::
Note card with a watercolor of Fresno's historic Einstein House commissioned by Virginia Eaton. The home currently houses the Marjaree Mason Center. The Einstein family were early Fresno pioneers and wealthy entrepeneurs. In the 1930s, they changed their name to Eaton to avoid association with Germany during the rise of Hitler. Lewis Eaton grew up in the house shown on the card. He became a major regional banker before selling Guarantee Savings to Glendale Federal Bank in the 1990s. Eaton and his family amassed the largest private collection of Rollin Pickford watercolors, purchasing more than 200 before Guarantee Savings was sold.